Application of finite elements using MATLAB to solve waveguide problems - Delgado León, Miguel Z. (2002)
The present work develops the Finite Element Method (FEM) as a program written in MATLAB code and its application for the numerical simulation of waveguides. The Helmholtz equationdiferential is determined by solving as the generalized eigenvalue problem and with MATLAB is simples. The numerical results is compared with the solution analitical of the rectangular waveguides, we obtained good results.